Effect of different clinical applications on physico-mechanical properties of composite resins - Gümüştaş, Burak; Güray Efes, Begüm (Universidade Federal de Uberlandia, 2018)
Although clinicians use fluoride agents to reduce the occurrence of caries, and surface sealing agents to protect composite restorations, the effects of these agents on composite resins have not yet been investigated. The goal of this study was to determine the effect of different surface applications (fluoride or surface sealant) on resin composites with different organic structures (Siloranes, Sonicfill, 3M Z550, Kalore). In this study, 120 discs and 120 bars made of composite resin were stored in water for three months before being thermally aged by cycling between 5°C and 55°C for 10,000 cycles. The discs were 15 mm in diameter and 1 mm thick; the bars were 25 × 2 × 2 mm. The surface sealant and fluoride were applied to the specimens, and evaluations were performed after 24h. Initial and final calculations were performed for flexural strength, microhardness, roughness, gloss, water sorption, and solubility. Silorane composite showed the lowest water sorption levels (p <0.05) for both initial and aged groups. Silorane and SonicFill composite groups showed the lowest solubility (p <0.05). Both before and after aging, the SonicFill group showed the highest values of flexural strength and microhardness. Silorane showed the highest roughness and lowest gloss values. Lower water sorption and solubility rates were seen on materials fabricated from hydrophobic monomers. High water sorption and solubility degrades the mechanical and surface properties. Fluoridation and surface sealant application can alter the surface properties but do not have any effect on the mechanical properties.

RESUMO: Embora os clínicos utilizem agentes de flúor para reduzir a ocorrência de cáries e agentes de vedaçãode superfície para proteger restaurações compostas, os efeitos desses agentes sobre as resinas compostas ainda não foram investigados. O objetivo deste estudo foi determinar o efeito de diferentes aplicações de superfície (fluoreto ou selante de superfície) em resinas compostas com diferentes estruturas orgânicas (Siloranes, Sonicfill, 3M Z550, Kalore). Neste estudo, 120 discos e 120 barras de resina composta foram armazenados em água por três meses antes de serem envelhecidos termicamente por ciclos alternados entre 5 °C e 55 °C por 10.000 ciclos. Os discos tinham 15 mm de diâmetro e 1 mm de espessura; as barras eram 25 × 2 × 2 mm. O selante de superfície e o flúor foram aplicados nos espécimes e as avaliações foram realizadas após 24 horas. Cálculos iniciais e finais foram realizados para resistência à flexão, microdureza, rugosidade, brilho, sorção de água e solubilidade. O compósito de silorano apresentou os menores níveis de sorção de água (p <0,05) para os grupos inicial e envelhecido. Os grupos compostos Silorane e SonicFill apresentaram a menor solubilidade (p <0,05). Tanto antes quanto depois do envelhecimento, o grupo SonicFill apresentou os maiores valores de resistência à flexão e microdureza. Silorane apresentou a maior rugosidade e menores valores de brilho. Baixas taxas de sorção e solubilidade da água foram observadas em materiais fabricados a partir de monômeros hidrofóbicos. A alta sorção e solubilidade da água degrada as propriedades mecânicas e de superfície. A fluoretação e a aplicação de selante de superfície podem alterar as propriedades da superfície, mas não afetam as propriedades mecânicas.
Efeito de diferentes aplicações clínicas nas propriedades físico-mecânicas de resinas compostas
Keywords: Acidulated Phosphate Fluoride; Adhesives; Mechanical Properties; Silorane Resins; Surface Properties; Fluoreto de Fosfato Acidulado; Adesivos; Proprieda des Mecânicas; Resinas de Silorano; Propriedades de Superfície